2013
DOI: 10.1111/j.1539-6975.2013.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Outstanding Claim Liabilities: The Role of Unobserved Risk Factors

Abstract: This article proposes a new method for estimating claim liabilities. Our approach is based on the observation from contract theory that there is information asymmetry between the insurer and the policyholder about the risks incurred by the latter. We show that unobserved heterogeneity allows for a form of experience learning that can reduce this asymmetry, which makes it easier for the insurer to distinguish between high‐risk and low‐risk claimants. We evaluate our approach in the context of disability insuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…The results of these studies show that firm size, ownership structure, mode of business and human capital are important factors affecting firm performance. Cummins and Weiss (1993) mentioned that claim settlement practices can cause inefficiency; later, Spierdijk and Koning (2014) suggested that insurers should respond to outstanding claims by setting aside this provision. This allows us to identify a gap in the literature and provides us with an opportunity to explore the impact of provision for outstanding claims on the efficiency of Takaful insurance.…”
Section: Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies show that firm size, ownership structure, mode of business and human capital are important factors affecting firm performance. Cummins and Weiss (1993) mentioned that claim settlement practices can cause inefficiency; later, Spierdijk and Koning (2014) suggested that insurers should respond to outstanding claims by setting aside this provision. This allows us to identify a gap in the literature and provides us with an opportunity to explore the impact of provision for outstanding claims on the efficiency of Takaful insurance.…”
Section: Efficiencymentioning
confidence: 99%
“…Although many papers (Cummins et al, 2017;Biener, Eling, & Jia, 2017) have investigated size as a possible common factor that influences the efficiency of insurers, our study provides accurate insight by looking at the effect of provision for outstanding claims on the efficiency and competitiveness of Takaful insurance. Spierdijk and Koning (2014) suggest that insurers should respond to outstanding claims by setting aside this provision has become a central subject in modern actuarial science. More interestingly, this paper examines the impact of efficiency on the competitiveness of Takaful insurers by attempting to provide novel research on the insurance sector.…”
Section: Introductionmentioning
confidence: 99%
“…To relax this restriction, model (3) is modified by allowing the density to vary with calender month of unemployment benefit entry. This is achieved by adopting another idea from actuarial sciences (compare Spierdijk and Koning, 2014). In particular, we use claim duration density estimates that are obtained from a duration model.…”
Section: Forecast Amentioning
confidence: 99%
“…Enhanced data requirements make it more complicated to implement and run these models in real business operations as data on all variables need to be available promptly. Similar to Spierdijk and Koning (2014), another extension could be made by adopting a duration model with frailty to allow for unobserved factors in the analysis.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation